Positivity of ExoU Gene of Type III Secretion System and Fluoroquinolone Resistance of Psedomonas aeruginosa from Sputum of Nosocomial Pneumonia Patients in Sanglah Hospital, Bali - Saputra, I Wayan Agus Gede Manik; Mertaniasih, Ni Made; Fatmawati, Ni Nengah Dwi (Folia Medica Indonesiana, 2018)
Pseudomonas aeruginosa is one of the Gram-negative rods bacteria that frequently cause nosocomial pneumonia. One of the main virulent effector proteins on Type III secretion system (TTSS) of P. aeruginosa is Exoenzyme U ( ExoU). ExoU works as a phospholipase A2 activity and exhibits lung tissue injury effect in pneumonia. As an antibiotic that has activity against P. aeruginosa, fluoroquinolone resistance has increased as many as three fold since the last decade. Infections caused by P. aeruginosa that are fluoroquinolone resistant and positive for ExoU gene show worse clinical outcome. The aim of this study was to determine the positivity of ExoU gene TTSS and fluoroquinolone resistance of P. aeruginosa that isolated from sputum of nosocomial pneumonia patients in Sanglah Hospital, Bali. P. aeruginosa isolated from sputum of patient that diagnosed as nosocomial pneumonia, isolates had been identified phenotypically by Vitek2 Compact system (bioMérieux, Inc., Marcy-l'Etoile - France), and then continued by genotypic detection by PCR. The susceptibility testing of P. aeruginosa isolates to Ciprofloxacin were conducted by Vitek2 Compact, whereas ExoU genes were detected by PCR. Fifty-three P. aeruginosa isolates were identified in this study, in which 35 isolates (66.1%) had ExoU gene and 22 isolates (41.5%) were resistant to Ciprofloxacin. Based on nosocomial pneumonia type, the highest proportion of isolates genotipically ExoU+ and phenotypically Ciprofloxacin were on VAP group accounted for 57.1% and 54.5%, respectively. Chi-square analysis showed significant correlation between Ciprofloxacin resistance and ExoU gene (p=0.001). As a conclusion, the positivity of ExoU+ isolates were more likely found in Ciprofloxacin resistant group.